Sistem Prediksi Kemacetan di Jalan Desa Menggunakan Metode Rule-Based System - Ghufronul A, M Mufti; Kustiyono (Institut Teknologi Garut, 2025)
Traffic congestion does not only occur in urban areas, but is also beginning to be felt in rural areas, especially on main roads connecting villages. This condition can hamper community mobility and inter-regional logistics distribution. To overcome this problem, this study specifically designed and implemented a congestion prediction system on village roads by utilizing historical traffic data, weather conditions, and community activities as the main parameters. The classification method used is the Rule-Based System algorithm. The results of this system can be used by village governments or local transportation managers to take preventive measures, such as adjusting logistics distribution schedules or deploying traffic officers. The system was tested in a village in Central Java, with a prediction accuracy of 87%. These results demonstrate the system's potential in assisting traffic management in villages.